Social Sciences in One Health: Insights From Multiple Worlds Perspectives on the Dam Rupture in Brumadinho-Brazil - Brandão, Ana Pérola Drulla; Sussai, Stefanie; Germine, Jéssica Alves de Lima; Eltz, Diego Duarte; Araújo, Aline (Frontiers in Public Health, 2021)
Concepts that integrate human, animal, and ecosystem health - such as One Health (OH) - have been highlighted in recent years and mobilized in transdisciplinary approaches. However, there is a lack of input from the social sciences in OH discussions. This is a gap to overcome, including in Latin America. Therefore, this paper incorporates recent studies from economics and anthropology to the debate, contributing to the opening of transdisciplinary dialogues for the elaboration of OH theory and practice. As a starting point, we explore the recent case of a tailings dam breach, making considerations about how and why this event was experienced in different ways by the affected Indigenous and non-Indigenous worlds. From economics, we show how different theories perceive and impact these different worlds, presenting some existing alternatives to the hegemonic thinking of domination and exploitation. From anthropology, we present the perspectivism concept, deriving from the field of relational ontologies, suggesting there are significant and inevitable disagreements - equivocations - among different worlds. Thus, we discuss how the social sciences can help address challenging factors that need to be considered in health approaches that intend to deal with complex global problems. In conclusion, OH should incorporate social science discussions, considering relating practice to the multiple realities in which a particular problem or conflict is inserted. Overcoming the barriers that hinder transdisciplinary dialogue is fundamental and urgent for an effective approach to the multiple and distinct interconnections among humans, animals and environments.